Dynamics of Consumer Protection Law in the Digital Era: Case Study on E-commerce in Indonesia - Safrida, Safrida (International Journal of Educational Research & Social Sciences, 2025)
The digital era has brought significant changes to commercial activities, including the rise of e-commerce as a key pillar of the digital economy in Indonesia. However, this development also poses various challenges in consumer protection, such as data security, information transparency, and dispute resolution. This article aims to analyze the dynamics of consumer protection law in the context of e-commerce in Indonesia through a case study approach. The study examines relevant regulations, such as the Consumer Protection Act and the Electronic Information and Transactions Act, and their implementation in safeguarding consumer rights. The findings reveal a disparity between the rapid growth of e-commerce and the readiness of regulations to adapt to technological advancements. Furthermore, gaps remain in law enforcement, particularly in monitoring digital platforms and effectively resolving disputes. This article recommends strengthening responsive regulations, enhancing public digital literacy, and fostering collaboration between the government, businesses, and consumers to create a secure and equitable e-commerce ecosystem.